Effect of Long-Term Climbing Training on Cerebellar Ataxia: A Case Series. (23rd November 2011) - Marianne Anke, Stephan; Sylvie, Krattinger; Jérôme, Pasquier; Shahid, Bashir; Thomas, Fournier; Dieter Georg, Ruegg; Karin, Diserens
Abstract : Background . Efficient therapy for both limb and gait ataxia is required. Climbing, a complex task for the whole motor system involving balance, body stabilization, and the simultaneous coordination of all 4 limbs, may have therapeutic potential. Objective . To investigate whether long-term climbing training improves motor function in patients with cerebellar ataxia. Methods . Four patients suffering from limb and gait ataxia underwent a 6-week climbing training. Its effect on ataxia was evaluated with validated clinical balance and manual dexterity tests and with a kinematic analysis of multijoint arm and leg pointing movements. Results . The patients increased their movement velocity and achieved a more symmetric movement speed profile in both arm and leg pointing movements. Furthermore, the 2 patients who suffered the most from gait ataxia improved their balance and 2 of the 4 patients improved manual dexterity. Conclusion . Climbing training has the potential to serve as a new rehabilitation method for patients with upper and lower limb ataxia.